Papers of the seminar on pesticides and food - Leslie, Kenneth A., ed. (NFNCCJ KingstonJM, 1987)
Papers discuss misuse of pesticides and effect of its residues on health and environment and outline roles and responsibilities of pesticide manufacturers, storage managers, distributors, supervisors, and applicators.